Recent Updates in Eating Disorders - Jáuregui-Lobera, Ignacio; Vicente Martínez-Quiñones, José (IntechOpen, 2023)
Recent Updates in Eating Disorders raises recent relevant issues about eating disorders and obesity that have led us to speak of an 'eating disorder society', especially among adolescents who are at the most vulnerable stage of life. It is important not only to be aware of the behaviours that occur before the emergence of an eating disorder, but also, from a clinical perspective, to talk about diagnostic criteria. It is also important to specify, as accurately as possible, the severity criteria and the presence of comorbidity, in order to establish better protocols for therapeutic action. We also address the issue of social media networks and their influence on the development of eating disorders (and many other problems). While this work is neither exhaustive nor extensive, we nevertheless hope it will be of interest and will open up further lines of study and research in the near future.